2011
DOI: 10.1080/10473289.2011.646049
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of recent state implementation plans for 8-hour ozone

Abstract: The development of state implementation plans (SIPs) for attainment of criteria pollutant standards is an integral component of air quality management in the United States. However, the content and efficacy of SIPs have rarely been examined systematically. Here, 20 SIPs developed in response to the 1997 8-hr ozone standard are reviewed as case studies of attainment efforts at the state level.Comparison of observed and model predicted ozone concentrations shows the U.S. Environmental Protection Agency (EPA) rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Some of the larger improvement in nonattainment regions than in attainment regions reflects a general trend of greater improvements at monitors that were more polluted in earlier years. The correlation between initial air quality and the magnitude of improvements parallels the findings of Pegues et al (2012), who showed that ozone and nitrogen dioxide (NO 2 ) reductions were greatest in regions where pollution levels were initially highest. The effect of nonattainment status can be isolated by considering monitors with similar initial DVs.…”
Section: Improvements In Nonattainment and Attainment Regionssupporting
confidence: 58%
See 3 more Smart Citations
“…Some of the larger improvement in nonattainment regions than in attainment regions reflects a general trend of greater improvements at monitors that were more polluted in earlier years. The correlation between initial air quality and the magnitude of improvements parallels the findings of Pegues et al (2012), who showed that ozone and nitrogen dioxide (NO 2 ) reductions were greatest in regions where pollution levels were initially highest. The effect of nonattainment status can be isolated by considering monitors with similar initial DVs.…”
Section: Improvements In Nonattainment and Attainment Regionssupporting
confidence: 58%
“…The weight-of-evidence determinations proved to be a helpful supplement to the attainment test in the attainment demonstrations considered here, as they allowed states to document localized controls and other considerations that counteracted false-alarm predictions of nonattainment. Caution is still needed in reviewing weight-of-evidence determinations, since for both ozone and PM 2.5 they have almost uniformly been used to suggest pollution levels will be lower than modeled; as documented by Pegues et al (2012), this led to false predictions of attainment in some ozone attainment demonstrations. Nevertheless, the cases considered here paint an overall picture of success in achieving the previous PM 2.5 standard, and substantial progress toward achieving the new one.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A few studies use population-weighted concentration (Hou et al, 2010) and personal exposure monitoring (Wu et al, 2010). Some studies opt to not assess exposure and instead apply statistical techniques that test for a change in health outcomes rates over the predefined time period of the intervention (Greenstone, 2004;Pegues et al, 2012;. Specific issues in relating air quality changes to exposures when conducting accountability studies include diagnosing both model uncertainty and parameter uncertainty in model selection (Morgenstern et al, 2012), missing data (Bell et al, 2011;Van Erp et al, 2011), and estimating baseline exposure for the no-control case that accounts for appropriate confounders (Health Effects Institute, 2003).…”
Section: Exposure/dosementioning
confidence: 99%